AB0379 Laboratory Safety of Adalimumab and Other Tumor Necrosis Factor Inhibitors in the Treatment of Rheumatoid Arthritis. (10th June 2014) - Pappas, D.A.; Shaw, J.W.; Chang, H.; Cifaldi, M.A.; Reed, G.W.; Garg, V.; Lacerda, A.P.; Mozaffarian, N.
Abstract : Background: Rheumatoid arthritis (RA) itself, as well as the disease-modifying drugs used to treat it, can have negative effects on various organ systems, manifesting as specific laboratory abnormalities which must be monitored for patient safety. Tumor necrosis factor inhibitors (TNFi) are effective for treating RA, but more data are needed about their association with laboratory parameters of interest. Objectives: This study was conducted to investigate the prevalence of specific laboratory abnormalities in patients with RA who initiate treatment with TNFi, including adalimumab (ADA). Methods: Data were abstracted from the Consortium of Rheumatology Researchers of North America (CORRONA) registry for biologic-naïve adult subjects with a diagnosis of RA who initiated treatment with ADA or other TNFi, were maintained on the same therapy for ≥6 months, and had results for ≥1 laboratory tests during the 6 months before and 6-12 months after initiating treatment. Prevalence rates for specific laboratory abnormalities available in the database (anemia, leukopenia, neutropenia, thrombocytopenia, and elevated creatinine) were calculated before and after treatment initiation. Logistic regression was applied to model abnormality rates as a function of treatment cohort, time (pre- vs. post-initiation), and the interaction of treatment with time while adjusting for patient demographic and clinical characteristics. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated. Results: Of the 1, 322 patients eligible for inclusion in the study, 424 (32.1%) were initiated on ADA, while 898 (67.9%) were initiated on other TNFi. Patients initiated on ADA were different than those initiated on other TNFi; ADA patients were younger (mean age 54.3 vs. 56.9 years, P<.001), more likely to be employed full time (49.2% vs. 40.2%, P=.002), less likely to be retired (18.9% vs. 26.1%, p=0.004) and less likely to be Medicare beneficiaries (19.8% vs 31.0% P<.001). There were no differences in the prevalence of laboratory abnormalities following initiation of treatment with either ADA or other TNFi. (Table 1 ). Conclusions: For specific safety parameters of interest in RA, our results suggest that treatment initiation with TNFi in a real-world clinical setting is not associated with a statistically significant increase in the rates of abnormal laboratory values. Results for patients initiated on ADA were similar to those for patients initiated on other TNFi, indicating that there is no difference in the safety profiles between ADA and other TNFi for the treatment of RA. Acknowledgements: The CORRONA RA registry has been supported through contracted subscriptions in the last two years by Abbvie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex and UCB.The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: D. Pappas Employee of: CORRONA, Inc., Paid instructor for: Novartis, J. Shaw Shareholder of: AbbVie, Employee of: Former AbbVie employee, H. Chang Consultant for: CORRONA, Inc., Employee of: Tufts Medical Center, M. Cifaldi Shareholder of: AbbVie, Employee of: AbbVie, G. Reed Employee of: CORRONA, Inc., V. Garg Shareholder of: AbbVie, Employee of: AbbVie, A. P. Lacerda Shareholder of: AbbVie, Employee of: AbbVie, N. Mozaffarian Shareholder of: AbbVie, Employee of: Former AbbVie employee DOI: 10.1136/annrheumdis-2014-eular.2051